Induction of T Cell Senescence by Cytokine Induced Bystander Activation - Abbas, Attiya A.; Akbar, Arne N. (Frontiers in Aging, 2021)
As people around the world continue to live longer, maintaining a good quality of life is of increasing importance. The COVID-19 pandemic revealed that the elderly are disproportionally vulnerable to infectious diseases and immunosenescence plays a critical role in that. An ageing immune system influences the conventional activity of T cells which are at the forefront of eliminating harmful foreign antigens. With ageing, unconventional end-stage T cells, that exhibit a senescent phenotype, amass. These senescent T cells deviate from T cell receptor (TCR) signaling toward natural killer (NK) activity. The transition toward innate immune cell function from these adaptor T cells impacts antigen specificity, contributing to increased susceptibility of infection in the elderly. The mechanism by which senescent T cells arise remains largely unclear however in this review we investigate the part that bystander activation plays in driving the change in function of T cells with age. Cytokine-induced bystander activation may offer a plausible explanation for the induction of NK-like activity and senescence in T cells. Further understanding of these specific NK-like senescent T cells allows us to identify the benefits and detriments of these cells in health and disease which can be utilized or regulated, respectively. This review discusses the dynamic of senescent T cells in adopting NK-like T cells and the implications that have in an infectious disease context, predominately in the elderly.